American health crisis : one hundred years of panic, planning, and politics - Halliwell, Martin (University of California Press, 2021)
"Despite enormous advances in medical science and public health education over the last century, access to health care remains a dominant issue in American life. U.S. health care is often hailed as the best in the world, yet the public health emergencies of today very often echo the public health emergencies of yesterday: the Great Influenza Pandemic of 1918-19 and COVID-19; the displacement of the Dust Bowl and the havoc of Hurricane Maria; the Reagan administration's antipathy toward the AIDS epidemic and the lack of accountability during the water crisis in Flint, Michigan. Spanning the period from the presidency of Woodrow Wilson to that of Donald Trump, American Health Crisis illuminates how--despite the elevation of health care as a human right throughout the world--vulnerable communities in the United States continue to be victimized by structural inequalities across disparate geographies, income levels, and ethnic groups. Martin Halliwell views contemporary public health crises through the lens of historical and cultural revisionings, suturing individual events together into a narrative of calamity that has brought us to our current crisis in health politics. American Health Crisis considers the future of public health in the United States and, presenting a reinvigorated concept of health citizenship, argues that now is the moment to act for lasting change"--Publisher's description.